SHAKESPEARE’S COMIC AND TRAGIC GENDER ISSUES: AN ATTEMPT AT TRANSGRESSION IN THE TAMING OF THE SHREW (1591) AND ROMEO & JULIET (1597) - Gonçalves, Davi (Revista Periódicus, 2019)
This article analyses Shakespeare’s literary discourse as an integral factor among the society wherein it was inserted. The overall context of my study is this precise dialogue between the literary structure and the structure of society. The symptoms that I allege literary texts tend to display are crucial for the effective functioning of the narratives herein analysed, and which consist thus in the specific context of my study. Such context consists in Shakespeare’s plays The Taming of the Shrew (1591) and Romeo & Juliet (1597), whose readings focus here specifically on the main characters of both narratives’ attempt at transgressing social borders. The comic and the tragic are not opposed, they are not poles apart in terms of meaning, effects, importance, and structure – in fact, in many occasions tragedy depends on comic stances and vice versa. My findings demonstrate how the frontiers dividing tragedy and comedy are not as concrete as it may seem – and trying to insert them within closed epistemological boxes might be detrimental for any fruitful reading of them. Shakespeare’s main characters in both plays might be read as a historical token of women’s unsuccessful endeavor to defeat repression.